2008
DOI: 10.1108/17506180810891627
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of types of special interest tour preferences and preference demographic variables analysis

Abstract: PurposeThe paper research objectives are: to investigate into the classification of special interest tour preferences in terms of their types and to compare whether consumers with different demographic attributes result in discrepancies in special interest tour preferences.Design/methodology/approachThose collected questionnaires that had incomplete answers and that had a significant response tendency or were left blank with no answers were eliminated. The required statistical methods are explained thus: this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Hui and Wan (2003) detected significant perceptual differences with regards to Singapore’s image. Furthermore, Sheng, Shen, and Chen (2008) discovered discrepancies in special-interest tour preferences when examining groups with different demographic attributes. It was found that age resulted in a significant difference and there was a negative correlation regarding types of physical adventure.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Hui and Wan (2003) detected significant perceptual differences with regards to Singapore’s image. Furthermore, Sheng, Shen, and Chen (2008) discovered discrepancies in special-interest tour preferences when examining groups with different demographic attributes. It was found that age resulted in a significant difference and there was a negative correlation regarding types of physical adventure.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Many past research works have indicated that tourists' imagery, or selection of and expectation for tourism purposes and events, is influenced by past behaviors and experiences (Joseph and Gilmore, 1998; Larsen, 2007; Weaver et al , 2007). On the other hand, tourist experience expectations or preferences for tourism will be affected by personal traits and states, such as demography (Sheng et al , 2008a) or lifestyle (Sheng et al , 2008b). In addition, with the prevalence of the internet, tourists can actively collect online information in advance and create experience expectations even before visiting a destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourists are passively included in such theoretical frameworks, and only in final investigations. Therefore, according to historical/artistic tourism in the classifications of Sheng et al (2008a), this study designed an experience expectations questionnaire that can reflect the actual situations of on‐site tourist experiences, and truthfully record tourists' opinions. This study investigates the factors of tourist experience expectations, and conducts a narrative analysis on these factors.…”
Section: Literature Reviewmentioning
confidence: 99%